2016
DOI: 10.1111/maps.12805
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle dynamics during the atmospheric entry heating of cosmic spherules

Abstract: Abstract-Cosmic spherules are unique igneous objects that form by melting due to gas drag heating during atmospheric entry heating. Vesicles are an important component of many cosmic spherules since they suggest their precursors had finite volatile contents. Vesicle abundances in spherules decrease through the series porphyritic, glassy, barred, to cryptocrystalline spherules. Anomalous hollow spherules, with large off-center vesicles occur in both porphyritic and glassy spheres. Numerical simulation of the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Tailed micrometeorites were first reported by Taylor et al () (Figure ) and later found among the TAM collection (Suavet et al, , Figure i; Suttle et al, ); their formation mechanism is unresolved. Metal beads, formed by the segregation of immiscible Fe–Ni metal (or Fe–Ni sulfides) from silicate melt (Genge & Grady, ), were found in 20.4% of S‐type cosmic spherules. Hollow spherules occur at a frequency of 1.6% and contain a single large off‐center vesicle (>40 vol %). They were first reported in Folco and Cordier () and later suggested by Genge () to form by rapid spin rates (of several thousand radians per second), potentially representing immature dust, recently released from their parent body, and whose fast rotation have not yet been slowed by magnetic dampening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailed micrometeorites were first reported by Taylor et al () (Figure ) and later found among the TAM collection (Suavet et al, , Figure i; Suttle et al, ); their formation mechanism is unresolved. Metal beads, formed by the segregation of immiscible Fe–Ni metal (or Fe–Ni sulfides) from silicate melt (Genge & Grady, ), were found in 20.4% of S‐type cosmic spherules. Hollow spherules occur at a frequency of 1.6% and contain a single large off‐center vesicle (>40 vol %). They were first reported in Folco and Cordier () and later suggested by Genge () to form by rapid spin rates (of several thousand radians per second), potentially representing immature dust, recently released from their parent body, and whose fast rotation have not yet been slowed by magnetic dampening.…”
Section: Resultsmentioning
confidence: 99%
“…• Hollow spherules occur at a frequency of 1.6% and contain a single large off-center vesicle (>40 vol %). They were first reported in Folco and Cordier (2015) and later suggested by Genge (2017) to form by rapid spin rates (of several thousand radians per second), potentially representing immature dust, recently released from their parent body, and whose fast rotation have not yet been slowed by magnetic dampening.…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 99%
“…], and in cosmic spherules [Genge ]). According to numerical modeling for cosmic spherules, for low peak temperature, vesicle migration within the melt is mostly controlled by the melt viscosity, whereas at high peak temperature (superheating, like those experienced in the fusion crust), the migration and coalescence of vesicles is controlled by the dynamic processes during transit through the Earth's atmosphere (Genge ). This implies that due to fast cooling, the vesicles in the fusion crust are quenched and stop migrating relatively soon after formation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, information is provided by the occurrence .5 (7) 6.7 (9) 14 avg = average of the indicated number (#) of spot analyses, with standard deviation; Avg ureilite* = average ureilite composition after Jarosewich (1990), only absolute content of selected elements (tot < 100); bdl = below detection limit. of large vesicles, suggesting degassing (e.g., fusion crust of a carbonaceous chondrite [Genge and Grady 1999], of lunar meteorites [e.g., Joy et al 2006], and in cosmic spherules [Genge 2017]). According to numerical modeling for cosmic spherules, for low peak temperature, vesicle migration within the melt is mostly controlled by the melt viscosity, whereas at high peak temperature (superheating, like those experienced in the fusion crust), the migration and coalescence of vesicles is controlled by the dynamic processes during transit through the Earth's atmosphere (Genge 2017).…”
Section: Cooling Rate(s) In the Fusion Crustmentioning
confidence: 99%
“…Initial trapping of gas is, therefore, likely to be efficient with initial vesicle abundances controlled by collapse of foams. Subsequent loss of vesicles by migration under the influence of deceleration, as discussed by Genge [], then decreases vesicle content with further heating.…”
Section: Vesicle Formation Mechanismsmentioning
confidence: 99%